Physiotherapy Students’ and Practice Educators’ Experiences of Using Placements Passports: A Tool to Enhance Collaboration on Placement - Ryan, Sarah-Jane; Morris, Jane (International Journal of Practice-based Learning in Health and Social Care, 2020)
Integral to physiotherapy students’ study are their practice placements. Placements form a mandatory part of students’ programmes of study. Practice learning is seen as an essential component of the curricula and as such is a key element of the students’ learning and development. The UK health service, which continues to provide the majority of practice learning opportunities for healthcare students, is experiencing unprecedented demand on services. Practice educators are reporting increasing pressure to maintain service provision whilst trying to support students in the practice setting. To maximise learning on placement, the placement passport was developed. This aims to support a more collaborative approach to the student’s learning in practice, by promoting a partnership between the practice educator and the student, and by encouraging and enabling the students to develop their skills of self-evaluation and self-directed learning, but also giving the practice educator the opportunity to try to tailor the experience to the student’s needs and wants. This study aims to explore students’ and practice educators’ experiences of using a placement passport in physiotherapy education. Five students and four practice educators attended one-off focus groups to explore their experiences. Findings suggested that the passport is a tool to support collaborative approaches to students’ learning, helping students and practice educators to bridge the gap between academia and the reality of practice. It also provided both with the opportunity to begin early dialogue around the students’ and practice educators’ expectations of the practice placement while acknowledging prior learning and development.